The Influence of Organizational Culture, Organizational Commitment, and Work Discipline on Employee Performance at Logistics Companies in Purworejo Regency - Aziza, Laela Nur; Gunawan, Hamzah (CV. Rayyan Dwi Bharata, 2024)
This study aims to identify and analyze the influence of organizational culture, organizational commitment, and work discipline on employee performance in Purworejo Regency. The sample for this study consisted of 100 respondents who are couriers from PT Pos Indonesia, JNE, JNT, Shopee Food, Grab, and Gojek. The results of the research instrument tests indicate that the data in this study are valid and reliable based on validity and reliability tests. The classical assumption tests produced a regression model free from multicollinearity, heteroscedasticity, and showed that the data were normally distributed. The research findings indicate that (1) organizational culture does not have a significant effect on employee performance, (2) organizational commitment has a significant effect on employee performance, and (3) work discipline has a significant effect on employee performance.